2020
DOI: 10.3389/fchem.2020.587207
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Gold(III) Compounds With Porphyrin or N-heterocyclic Carbene Ligands

Abstract: The use of gold in medicine has a long history. Recent clinical applications include anti-inflammatory agents for the treatment of rheumatoid arthritis (chrysotherapy), and is currently being developed as potential anticancer chemotherapeutics. Gold(III), being isoelectronic to platinum(II) as in cisplatin, is of great interest but it is inherently unstable and redox-reactive under physiological conditions. Coordination ligands containing C and/or N donor atom(s) such as porphyrin, pincer-type cyclometalated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…The porphyrin ligand can stabilize the electrophilic gold( iii ) ion against demetalation under physiological conditions. 176,177 Apart from tetradentate porphyrins, the electrophilic gold( iii ) ion can also be stabilized by pincer-type ligands containing deprotonated C-donor atom. 178,179 Zhang et al reported a panel of cyclometalated gold( iii ) complexes bearing a C-deprotonated bidentate ligand with promising in vitro cytotoxicity toward different cancer cell lines, which was associated with the induction of ER stress.…”
Section: Gold(iii) Complexes As Anticancer Agentsmentioning
confidence: 99%
“…The porphyrin ligand can stabilize the electrophilic gold( iii ) ion against demetalation under physiological conditions. 176,177 Apart from tetradentate porphyrins, the electrophilic gold( iii ) ion can also be stabilized by pincer-type ligands containing deprotonated C-donor atom. 178,179 Zhang et al reported a panel of cyclometalated gold( iii ) complexes bearing a C-deprotonated bidentate ligand with promising in vitro cytotoxicity toward different cancer cell lines, which was associated with the induction of ER stress.…”
Section: Gold(iii) Complexes As Anticancer Agentsmentioning
confidence: 99%
“…NHC complexes have proven to be suitable catalysts for dihydroalkoxylation and hydroamination reactions 204 and to be active anti-cancer agents. 205,206 Gold(III) NHC complexes are synthesized by oxidation of the relevant gold(I) NHC complex, using as an oxidizing agent PhICl2, 207,208 halogens (Cl2, Br2, I2), [208][209][210] CsBr3 211 and N-halosuccinimides (Scheme 1.6). 212 Alternatively disproportionation of gold(I) NHC complexes using a sacrificial gold(I) compound leads to the formation of gold(III) NHC complexes.…”
Section: Gold(iii) Nhc Complexesmentioning
confidence: 99%
“…Gold(III) complexes have been intensively investigated as potential antitumor agents due to their similarities with platinum(II) complexes ( Rana et al, 2018 ; Radisavljević and Petrović, 2020 ; Tong et al, 2020 ). Only recently, the growing threat of MDR pathogens has drawn attention to the application of these compounds also as antimicrobials ( Glišić and Djuran, 2014 ; Dominelli et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%